Not sure how to approach this one, does anyone have an idea?
BTW, in the top line it should read xz-plane, not xy.
(try using the X2 tag just above the Reply box )
Forget all the stuff about the cylinder …
the question is simply to prove that if you rotate z = e-x2 about the z-axis, you get z = e-x2-y2 …
that's easy, isn't it?
ok … what does "rotate z = f(x) about the z-axis" mean? … how would you express the instruction as an equation?
Yup! And the equation of a circle is … ?
"Since each point on the graph z = e-r2 will generate a circle when rotated about the z-axis, and the equation for a circle is r2 = x2 + y2, we can make this substitution into our equation for r2, giving us z = e-(x2+y2)."